Urgensi Pelestarian Lingkungan Dalam Menghadapi Krisis Ekologis Global - Abdul Aziz, Nurdin (CV RIFAINSTITUT, 2025)
The global ecological crisis increasingly reveals its contours through the rising frequency of natural disasters, the depletion of resources, and the disruption of ecosystem balance. In this context, environmental preservation is no longer a mere moral discourse but an imperative for civilization. This article examines how environmental conservation must be positioned as a strategic foundation in confronting climate change and the growing complexity of ecological degradation. Using a qualitative-analytical approach, the study explores the interrelation between human behavior, public policy, and ecological dynamics that constantly influence one another. The findings indicate that the success of ecological crisis mitigation relies heavily on the integration of ecological values into development patterns, resource governance, and collective societal awareness. Thus, environmental preservation becomes a meeting point between scientific insight, ethical commitment, and practical action—each essential to be carried out consistently and sustainably. Through a deeper understanding of this urgency, it is hoped that new development models may emerge, addressing economic demands while ensuring the continuity of the Earth as our shared home.